Biological and Phytochemical Responses of Trigonella foenum-graceum Plants to Silver Nanoparticles. Issue 3 (4th February 2023) - Talei, Daryush; Khayam Nekouei, Mojtaba; Kadkhodaei, Saeid
ABSTRACT: The present study aimed to investigate the effects of applying different concentrations of AgNPs on plant yield, protein and phytochemical compound in Trigonella foenum-graecum . For this purpose, an experiment was carried out based on a completely randomized design (CRD) with six concentrations of AgNPs (0, 2.5, 5, 10, 20 and 40 mg/L). The results showed that the highest biomass (2.14 ± 0.02 g) and chlorophyll content (52.80 ± 2.51 µg·g −1 FW) were obtained in 10 mg/L of AgNPs, while the highest protein content (3.3 ± 0.12 mg·g −1 FW) was obtained in 20 mg/L of AgNPs. The highest amount of trigonelline (TG) and nicotinic acid (NT) contents were obtained in 10 mg/L of AgNPs. Treatments with an AgNPs concentration higher than 10 mg L −1 led to reduced growth, biomass, chlorophyll, protein, TG and NA contents. AgNPs application caused considerable increase in seed yield and TG content. Therefore, the use of low concentration of AgNPs (10 mg/L) could be recommended to improve the T. foenum-graecum growth, biomass, protein content and phytochemical compound production.